Mathematics

Question

the concept and full method
the concept and full method

1 Answer

  • Answer:

    Step-by-step explanation:

    This kinda looks like the limiting definition of a derivative.  

    Anyway, what we are doing with the f(2 + h) is evaluating f(x) with 2+h in place for x.  That looks like this:

    f(2 + h) = 2(2 + h) - 3 which simplifies to

    f(2 + h) = 4 + 2h - 3 which simplifies to

    2h + 1

    From that we are subtracting f(2).  What we are doing with that is evaluating f(x) with 2 in place for x.  That looks like this:

    f(2) = 2(2) - 3 which simplifies to

    f(2) = 4 - 3 which simplifies to

    f(2) = 1.  Now put those together over h to get:

    [tex]\frac{f(2+h)-f(2)}{h}=\frac{2h+1-1}{h}=\frac{2h}{h}=2[/tex]

NEWS TODAY